PPP2R3A-RGS19 interaction links Wnt/β-catenin signaling to pathological cardiomyocyte apoptosis in heart failure - Shuang Qin; Lingge Su; Jing Gao; Chunyan Wu; Yating Zhang; Hongqiong Shi; Guibo Song (Molecular Biology Reports, 2026)

Stability strategy of astaxanthin in Antarctic krill muscle: Insights from proteomics and docking simulation - Xixi Wang; Dong Su; Yating Zhang; Qinshuai Hou; Junkui Miao; Xiaofang Liu; Changfeng Qu; Kailiang Leng (Food Research International, 2026)

Hydrolyzed konjac glucomannan retards egg white protein digestion via glycosylation -driven gastric texture and rheology modulation - Lulu Guo; Yicheng Guo; Yating Wu; Shende Hu; Xiaosan Wang; Luping Gu; Cuihua Chang; Junhua Li; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2026)

Hydrogen and methane production characteristics and toxic component degradation behaviors of microbial electrolysis cells treating hydrothermal wastewater - Zhenghui Zhao; Yating Wang; Chunbai Wang; Jiazhen Su; Jing Xi; Qianqian Yin; Lichao Ge; Ruikun Wang (Bioresource Technology, 2026)

pH-Shifting combined with heat treatment regulates the aggregate structure and interfacial functional properties of egg white protein microparticles powder - Yating Wu; Yicheng Guo; Junhua Li; Luping Gu; Yanjun Yang; Cuihua Chang; Yujie Su (Food Research International, 2026)

A Quad-Polarimetric SAR image reconstruction network and wetland classification fusing optical texture and polarization information - Yating Zhan; Yujun Wang; Ke Song; Yiming Su; Xin Rong; Gui Zhou; Yefei Zhu; Ziqiao Xu (International Journal of Remote Sensing, 2026)

High porosity poly(porous liquid)s based on multiple hydrogen bonds for rapid ammonia response - Yisong Liu; Jing Zhang; Shizhang Li; Fangfang Su; Yangyang Xin; Yating Zhang; Jinliang Xie; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2026)

Integrating filtration, pollutant adsorption, and thermal management for enhanced respiratory health: A synergistic framework for next-generation protective masks - Yating Tang; Yun Su; Yiwei Wu; Zhuoling Yu; Mengxian Xu; Miao Tian; Jun Li (Building and Environment, 2026)

The impact of digital factor allocation on urban resilience under energy constraints in China - Sisi Zhang; Yingxin Su; Yating Zhong; Qi Cui (Environment, Development and Sustainability, 2026)

Bearing behaviour of S700 high strength steel bolted connections after exposure to elevated temperatures - Qianzhi Chen; Ziyi Wang; Andi Su; Yating Liang; Ou Zhao (Engineering Structures, 2026)

UiO-66 porous liquids with synergistic catalytic effects for promoting efficient CO2 conversion - Yaru Lu; Ruyu Bai; Dechao Wang; Yangyang Xin; Weirui Zhang; Fangfang Su; Zheng Dong; Wendi Fan; Yating Zhang; Fangli Yu; Xin Li; Yingying Zhou; et al. (Chemical Engineering Journal, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Using machine learning to deeply analyze the critical role of trace element additives in anaerobic digestion and guide the optimization of addition strategies - Yating Yu; Yi Zhang; Yijing Feng; Zheng Hao Leong; Junting Pan; Jianping Su; Yeqing Li (Water Research, 2026)

Cloning and functional study of NADPH-cytochrome P450 reductases and ent-kaurene oxidase from Rhododendron Molle G. Don - Xinmeng Wang; Zheng Liu; Rongfeng Wang; Hao Tang; Ping Su; Xianan Zhang; Xiaoyi Wu; Shurui Zhao; Jiadian Wang; Yating Hu; Luqi Huang (Physiology and Molecular Biology of Plants, 2026)

The effect of short-term storage on Antarctic krill (Euphausia superba) quality: Insights into microbial characteristics, volatile flavor compounds, trimethylamine oxide and its derivatives - Xixi Wang; Xinyu Ma; Dong Su; Yating Zhang; Junkui Miao; Xiaofang Liu; Yuan Yu; Kailiang Leng (Food Research International, 2025)

Testing, numerical modelling and design of stainless steel built-up box-sections under interior-one-flange loading - Yannan Jing; Ke Jiang; Andi Su; Yating Liang; Ou Zhao (Engineering Structures, 2025)

Heteroaggregation of functionalized nanoplastics with Al2O3 particles in aquatic environments - Xia Liu; Yating Zhao; Tongtao Yue; Bo Gao; Xing Guo; Meng Wang; Wenli Su; Chu Wang; Lu Liu; Yanhui Dai; Zhenyu Wang; Jian Zhao; et al. (Chemical Engineering Journal, 2025)

Indoor use of consumer chemical products and its link to depression and anxiety among college students in 297 chinese cities - Kai Su; Chunliang Wang; Linmin Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Qing Li; Runhua Zhou; Zan Lu; Dingwen Li; Yating Xie; et al. (Building and Environment, 2025)

Comparative evaluation of maize chromosome pretreatment using cold water and 8-hydroxyquinoline - Lulu Hou; Yating Su; Shixin Li; Haidong Yu; Yuhui Sun (Planta, 2025)

Highly sensitive ferroelectric photodetectors decorated with Ag2O cluster-quantum dots - Xiaoxu Bao; Yating Su; Rumei Song; Li Zhen; Shifeng Zhao; Yulong Bai (Chemical Engineering Journal, 2025)

Multifunctional bilayer electrocatalytic membrane with high permeability and antifouling property for efficient removal of dye from water - Yuan Zhu; Gege Zhao; Tianqi Du; Miao Zhang; Chengcheng Li; Xing Su; Yating Ji; Zaisheng Cai; Yaping Zhao (Journal of Water Process Engineering, 2025)

Altered mammary gland development and pro-tumorigenic changes in young female mice following prenatal BPAF exposure - Xiaotong Ji; Jiande Li; Weiwei Wang; Peilin Li; Haoyang Wu; Linzhuo Shen; Lihong Su; Peiyun Jiang; Yating Li; Xiaoyun Wu; Yuchai Tian; Yu Liu; et al. (Environmental Research, 2025)

Gelatin-crosslinked millard reaction products of sodium caseinate/ maltodextrin enhances the encapsulation efficiency and stability of krill oil microcapsules - Yating Zhang; Kailiang Leng; Xixi Wang; Zipeng Zhang; Dong Su; Ling Zhao; Xiaofang Liu; Yuan Yu; Junkui Miao; Yueqin Yu (Food and Bioproducts Processing, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

A comprehensive study of the colloidal properties, biocompatibility, and synergistic antioxidant actions of Antarctic krill phospholipids - Dong Su; Xixi Wang; Xiaofang Liu; Junkui Miao; Zipeng Zhang; Yating Zhang; Ling Zhao; Yuan Yu; Kailiang Leng; Yueqin Yu (Food Chemistry, 2024)

Long-Term Spatiotemporal Characteristics of Ulva prolifera Green Tide and Effects of Environmental Drivers on Its Monitoring by Satellites: A Case Study in the Yellow Sea, China, from 2008 to 2023 - Yating Zhan; Zhongfeng Qiu; Yujun Wang; Yiming Su; Yin Li; Yanmei Cui; Shuai Qu; Peng Wang; Xin Rong (Journal of Marine Science and Engineering, 2024)
Ulva prolifera (U. prolifera) green tide outbreaks have occurred in the Yellow Sea of China for many years, causing serious losses to marine ecology and the marine economy. The monitoring and tracking of U. prolifera green tide is a crucial aspect of marine ecological disaster prevention and control management. This paper aims to investigate the spatiotemporal distribution changes in U. prolifera green tide in the Yellow Sea throughout its life cycle. A survey of the Yellow Sea from 2008 to 2023 was conducted using multi-source remote sensing images. Long-term monitoring and analysis of U. prolifera revealed the evolution process of the green tide, including the early development, outbreak, decline, and extinction stages, considering time, space, and frequency of occurrence. Additionally, this study examined peak coverage change patterns over the past 16 years and analyzed the influence of environmental factors such as sea surface temperature and sea surface wind field on the development of U. prolifera. The research results serve as a valuable reference for the monitoring, early warning, and scientific prevention and control of U. prolifera green tide in the Yellow Sea, as well as other similar marine disaster areas.

Grey matter structural alterations in anxiety disorders: a voxel-based meta-analysis - Han Liu; Zeqi Hao; Shasha Qiu; Qianqian Wang; Linlin Zhan; Lina Huang; Youbin Shao; Qing Wang; Chang Su; Yikang Cao; Jiawei Sun; Chunjie Wang; et al. (Brain Imaging and Behavior, 2023)

Resource curse hypothesis and economic growth: A global analysis using bootstrapped panel quantile regression analysis - Yating Guo; Wing-Keung Wong; Nan Su; Wafa Ghardallou; Juan Carlos Orosco Gavilán; Pham Thi Minh Uyen; Phan The Cong (Resources Policy, 2023)

Spatio-temporal variation of soil microplastics as emerging pollutant after long-term application of plastic mulching and organic compost in apple orchards - Yuanji Wang; Li Liu; Shan Cao; Jing Yu; Xiangyu Li; Yating Su; Gaochao Li; Hua Gao; Zhengyang Zhao (Environmental Pollution, 2023)

Network analysis of eight industrial symbiosis systems - Yan Zhang; Hongmei Zheng; Han Shi; Xiangyi Yu; Gengyuan Liu; Meirong Su; Yating Li; Yingying Chai (Frontiers of Earth Science, 2016)

RNA interference-mediated repression of SmCPS (copalyldiphosphate synthase) expression in hairy roots of Salvia miltiorrhiza causes a decrease of tanshinones and sheds light on the functional role of SmCPS - Qiqing Cheng; Ping Su; Yating Hu; Yunfei He; Wei Gao; Luqi Huang (Biotechnology Letters, 2014)